Overview of Mrs. Primipara's level of knowledge about exclusive breastfeeding in the working area of the Bowong Cindea Pangkep Health Center - Antika, Rindi; Rahmai, Siti; Handayani, Tut (Bantayang Omni Cendekia, 2024)
Background: Lack of maternal knowledge about the benefits of breastfeeding and lactation from pregnancy to childbirth Objective: This study aims to determine the picture of the level of knowledge of primipara mothers about exclusive breastfeeding in the working area of the bowong cindea Pangkep health center. Methods: This research is a type of quantitative research with a descriptive design of survey methods, which was carried out on August 3-29, 2022 and the samples used in this study were 71 samples obtained by the simple random sampling method, with data collection using questionnaires. Results: Based on the results of data analysis, it was found that from 71 respondents, based on the age of most respondents aged 17-25 years, as many as 45 people (63.4%). Based on education, most respondents had junior high school education as many as 24 respondents (33.8%). Based on occupation, IRT was 46 respondents (64.8%). Conclusion: The level of knowledge of primipara mothers about exclusive breastfeeding in the working area of the bowong cindea Pangkep health center. Most of the knowledge level is less at 48 people (67.6%).